Dietary inflammatory index is associated with metabolic dysfunction-associated fatty liver disease among United States adults - Yan, Jing; Zhou, Jun; Ding, Yuanyuan; Tu, Chuantao (Frontiers in Nutrition, 2024)
Background: Metabolic dysfunction-associated fatty liver disease (MAFLD) is presently the most prevalent chronic liver disorder globally that is closely linked to obesity, dyslipidemia metabolic syndrome, and type 2 diabetes mellitus (T2DM). Its pathogenesis is strongly associated with inflammation, and diet is a major factor in reducing inflammation. However, current research has focused primarily on exploring the relationship between diet and NAFLD, with less research on its link to MAFLD.In this research, using dietary inflammatory index (DII) as a measure to assess dietary quality, we analyzed the relationship between diet and MAFLD. Data from the National Health and Nutrition Examination Survey (NHANES) 2017-2018, including 3,633 adults with complete DII and MAFLD, were used to develop cross-sectional analyses. Logistic regression analysis was adapted for investigating the relationship between DII and MAFLD development. Additionally, subgroup analysis and threshold effect analysis were carried out.A positive link between DII and MAFLD was found in the fully adjusted model (OR = 1.05; 95%CI, 1.00-1.11, p < 0.05). Subgroup analysis indicated that there was no significant dependence for the connection between DII and MAFLD except for the subgroup stratified by age.Compared with other age groups, people with MAFLD had 20% higher DII scores than non-MAFLD participants in those aged 20-41 years old (OR = 1.20; 95%CI, 1.08-1.33, p < 0.001). Furthermore, we found a U-shaped curve with an inflection point of 3.06 illustrating the non-linear connection between DII and MAFLD.Conclusions: As a result, our research indicates that pro-inflammatory diet may increase the chance of MAFLD development, thus improved dietary patterns as a lifestyle intervention is an important strategy to decrease the incidence of MAFLD.